Understanding buyers' loyalty to a C2C platform: the roles of social capital, satisfaction and perceived effectiveness of e‐commerce institutional mechanisms. (5th June 2015) - Huang, Qian; Chen, Xiayu; Ou, Carol Xiaojuan; Davison, Robert M.; Hua, Zhongsheng
Abstract: Drawing upon social capital theory, this study aims to investigate how different dimensions of social capital affect online buyers' satisfaction and ultimately boost their loyalty to a Consumer‐to‐Consumer (C2C) platform. Specifically, we propose that three dimensions of social capital (i.e., cognitive, structural and relational capital) contribute positively to the two types of online buyers' satisfaction (i.e., economic and social satisfaction). In addition, we posit that perceived effectiveness of e‐commerce institutional mechanisms (PEEIM) moderates the relationships between economic and social satisfaction and buyers' loyalty to the platform. Three hundred buyers on the Consumer‐to‐Consumer platform, TaoBao, were surveyed to test the proposed model. The results suggest that buyers' evaluation of social capital with the community of sellers can enhance their satisfaction with the sellers, which subsequently affect their loyalty to the platform. Furthermore, perceived effectiveness of e‐commerce institutional mechanisms negatively moderates the effect of economic satisfaction and positively moderates the effect of social satisfaction on buyers' loyalty to the platform. The theoretical contributions and practical implications are discussed.